The Effects of Strategic Absorptive Capacity, Business Sustainability, and Market Expansion Strategy on Business Performance of Iced Tea MSMEs in DKI Jakarta - Esa Cahaya Purnomo; Hilwa Karimah; Nazwa Abidin Yunus (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
Micro, Small, and Medium Enterprises (MSMEs) operating within the iced tea beverage industry in DKI Jakarta are increasingly confronted with heightened market competition and intensified demands to adapt to evolving market dynamics and sustainability imperatives. These challenges necessitate the development of strategic capabilities, most notably the capacity to assimilate external knowledge, incorporate sustainable business practices, and expand market reach, all of which are critical to enhancing business performance. The objective of this study is to investigate the influence of business sustainability on strategic absorptive capacity, assess the subsequent impact of strategic absorptive capacity on market expansion strategies and business performance, and explore the mediating role of strategic absorptive capacity in the relationship between business sustainability and business performance. To achieve these aims, this research employs a quantitative methodology, utilizing survey data collected from 598 iced tea MSMEs located in DKI Jakarta. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS version 23. The findings reveal that business sustainability exerts a significant positive influence on strategic absorptive capacity. Additionally, strategic absorptive capacity was found to positively affect both market expansion strategy and business performance. Perhaps most notably, strategic absorptive capacity functions as a complete mediator in the relationship between business sustainability and business performance. These results underscore the critical role of developing strategic absorptive capacity as a pivotal mechanism for fostering sustainability and bolstering competitiveness among MSMEs.